TINJAUAN PROSEDUR PENGGAJIAN PEGAWAI TETAP PADA PUSDIKLAT BADAN PUSAT STATISTIK - Frilya Anggraeni Heryamsah (2023)
Procedure is a phase of a process to complete an activity. Procedures help producuse efficiency in the process of completing such activities. Salary is the payment received by an employee in return for service rendered to the company or agency. Salaries are on of the important things for employees and companies because salaries can influence the performance of employees carrying out their duties and responsipilities. The payroll procedure makes the distribution of salaries to employees well-coordinated. The collection of data and information on the procedure of employment of employees remains in Education and Training Agency for the Central Bureau of Statistics using methods of library study and observation. With data processing techniques is qualitative descriptive analysis. The payroll procedure in Education and Training Agency for the Central Bureau of Statistics is carried out by several related sections as well as the documents used. Payroll in Education and Training Agency for the Central Bureau of Statistics, which is a government agency, is called official spending. The salary process has been passed according to the stages in making submissions for payment of staff expenses. Also with the documents used and related parts.